Building a family ontology to meet consistency criteria - Tan, Mee Ting (2015)
Semantic web is an extension of the current web in which the existing information on the web are organized and encoded more meaningfully using ontology language, thus enabling effective communication among machines and humans. Ontology is the backbone of the semantic web that contributes to knowledge sharing among intended parties over distributed systems around the world. In the past few years, semantic web has been widely accepted by a variety of fields for better knowledge representation, communication, sharing and reasoning on the web. Now, there are existing genealogical ontologies proposed by different groups of researchers once semantic web has emerged as third generation of the web. However, existing ontologies still lack certain important concepts and properties to support the domain of family relations. This may lead to the inability of the ontology to deliver full potential of exchanging family history information among all interested parties. Moreover, existing ontologies do not employ the full potential of SWRL rules to reason the individuals within the ontology. The main aim of this research is to build a new Family Ontology which obeys the consistency criteria. Consistency checking ensures there are no contradictory concepts found within the resulting ontology. The consistency of Family Ontology will be evaluated using FACT++, HermiT and Pellet reasoners. By augmenting the additional axioms and testing the resulting ontology thoroughly using reasoner tools, the proposed Family Ontology is expected to achieve a consistency of 100%.This research is meaningful and significant to all humans since everyone has his or her own unique family history. The proposed ontology also facilitates effective and efficient communication among all intended parties since shared vocabularies and standards are employed by the proposed ontology.